The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/joa.13358
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, ontogeny, and evolution of the archosaurian respiratory system: A case study on Alligator mississippiensis and Struthio camelus

Abstract: The avian lung is highly specialized and is both functionally and morphologically distinct from that of their closest extant relatives, the crocodilians. It is highly partitioned, with a unidirectionally ventilated and immobilized gas‐exchanging lung, and functionally decoupled, compliant, poorly vascularized ventilatory air‐sacs. To understand the evolutionary history of the archosaurian respiratory system, it is essential to determine which anatomical characteristics are shared between birds and crocodilians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…This recent research shows that some presumed ‘bird-like’ respiratory features, such as unidirectional air flow, are actually plesiomorphies characterizing much larger groups ( Schachner et al, 2014 ; Farmer and Sanders, 2010 ) and highlights the diversity of ways in which multiple anatomical systems interlink to effectively ventilate the lungs. New work on the pulmonary anatomy of the ostrich ( Struthio camelus ) has demonstrated that PSP relationships with the respiratory system in extant birds may not be as straightforward as previously thought ( Schachner et al, 2021 ), and reconstructions of dinosaur lungs that directly follow a standardized avian bauplan may need to be reconsidered. Additionally, primitive features like gastralia, simple sterna, and ‘propubic’ pelves impede attempts at completely superimposing the highly derived physiology of birds onto comparatively less-specialized clades like non-avian theropods and sauropods.…”
Section: Discussionmentioning
confidence: 99%
“…This recent research shows that some presumed ‘bird-like’ respiratory features, such as unidirectional air flow, are actually plesiomorphies characterizing much larger groups ( Schachner et al, 2014 ; Farmer and Sanders, 2010 ) and highlights the diversity of ways in which multiple anatomical systems interlink to effectively ventilate the lungs. New work on the pulmonary anatomy of the ostrich ( Struthio camelus ) has demonstrated that PSP relationships with the respiratory system in extant birds may not be as straightforward as previously thought ( Schachner et al, 2021 ), and reconstructions of dinosaur lungs that directly follow a standardized avian bauplan may need to be reconsidered. Additionally, primitive features like gastralia, simple sterna, and ‘propubic’ pelves impede attempts at completely superimposing the highly derived physiology of birds onto comparatively less-specialized clades like non-avian theropods and sauropods.…”
Section: Discussionmentioning
confidence: 99%
“…3D surface models were segmented in Avizo 7.1 and 2020.3 (Thermo Fisher Scientific) following the methods established for extant archosaur lungs (Farmer & Sanders, 2010; Lawson et al, 2021; Sanders & Farmer, 2012; Schachner et al, 2013, 2017, 2021). For a detailed description of the segmentation methodology used, see Lawson et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative measurements of the airways were collected from the DICOM editor and viewer OsiriX MD (http://www.osirix-viewer.com) and are included in Table S1. These measures have been established in previous work (Lawson et al, 2021; Schachner et al, 2021), and were based upon hypothesized homologous structures in other crocodilians (Farmer, 2015b; Sanders & Farmer, 2012; Schachner et al, 2013, 2021), as well as developmental work on reptiles and birds (Broman, 1939; Locy & Larsell, 1916a, 1916b). All measures were completed in the 3D MPR viewer of OsiriX.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations